(untitled) (International Journal of Engineering and Computer Science, 2018)
Now cyber-attacks are increasing because existing security systems are not able to identify them. The cyber attacks had purposes of disclosing personal information by attacking the PC and to reduce the system. The goal of recent heavy blows. attacks has changed from disclosing information and destruction of services to attacking large-scale systems such as analytic infrastructures. The defense technologies to counter these attacks are build on patterns matching methods which are very limited. This reality, The event of new and previously unknown attack, detections rate become very low. To keep safe from these unknown attacks, which unable to identified with existing technology, We proposed the new model based on big data analysis techniques that can obtain information from a variety of sources to identify future attacks. The model base on the future Advanced Persistent Threat detection and prevention system implementations.